Validity of ProQOL-5 Nepali Version: Burnout is Largely a Western Concept for Nepali Doctors - Adhikari, Yubaraj; Senft, Birgit; Poudyal, Bhava (NPRC Journal of Multidisciplinary Research, 2025)
This study examined the validity and reliability of the Nepali version of ProQOL-5 (N-ProQOL-5). A survey design was applied, and 547 Nepali doctors responded. CFA results showed non-retention of burnout symptomology in the Nepali population due to poor factor loading. The symptomology of STS and CS were tested, and five items of each construct were retained. The fit indices scores through CFA of a bi-factor model of N-ProQOL-5 showed the best fit: SMRs, RMR, and RMSEA measured less than 0.08, and the scores for NFI, TLI, AGFI, and CFI were above .90. The reliability coefficients of STS and CS subscales of N-ProQOL-5 were 0. 855 (p = 0.05), 0.852 (p = 0.05) respectively. Convergent and discriminant validity of STS and CS subscale of N-ProQOL-5 were established. The tool is valid and reliable to use in the Nepali population, however, the construct for Burnout was not relevant.